Comparison of Cultured S.Aureus and E.coli DNA Concentrations on Growth Media of Luria Bertani and Nutrient Broth - Trisiswanti, Trisiswanti; Arista, Anggi Maulia; Rizqita, Eza Alfian; Sugimin, Sugimin; Oxi, Rizki Yulia (Proceeding Series of International Conference on Arts and Humanities, 2022)
This study aimed to describe the comparison of cultured S.aureus and E.coli DNA concentration on growth media of Luria bertani and Nutrient broth. S.aureus and E.coli bacteria that have been cultivated on Luria Bertani (LB) and Nutrient Broth (NB) media, after measuring their absorbance values at a wavelength of 620 nm, have quite high absorbance values. For S. aureus bacteria which are gram-positive bacteria, Luria Bertani (LB) media is the best medium for cultivation, because the absorbance value is 1.324 ± 0.500, while S. aureus cultivated on Nutrient Broth (NB) growth media has a lower absorbance value. ie 1.047 ± 0.500 which means the highest cell density or optical density (OD) for S.aureus was cultivated on Luria Bertani (LB). The highest DNA concentration was found in NB E.coli isolates at 9.50 ng/µl. The best level of DNA purity was found in the isolates of NB S.aureus, which was 1.89 based on the A value of 260/280, while for the isolates LB E.coli, NB E.coli, and LB S.aureus were also good, but there were few contaminants so that A score of 260/280 produces a value below 1.8 and more than 2.0.